2008
DOI: 10.2139/ssrn.1280169
|View full text |Cite
|
Sign up to set email alerts
|

Labour Market Outcomes of Second Generation Immigrants: How Heterogeneous are They Really?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…However, some authors have cautioned against the use of such a 'pan-ethnic' term, as it refers to a very heterogenous group (Vathi, 2015;Portes and Zhou, 1993). Thus, the category of second-generation migrants should not be considered a homogeneous one; rather, one in which subgroups experience outcomes that are better or worse than, or equal to, those of the comparable native population (Schurer, 2008). Eckstein (2002) argues that migrant generations are influenced by the different social conditions they experience in their pre-and post-migration times.…”
Section: Defining Second-generation Migrantsmentioning
confidence: 99%
“…However, some authors have cautioned against the use of such a 'pan-ethnic' term, as it refers to a very heterogenous group (Vathi, 2015;Portes and Zhou, 1993). Thus, the category of second-generation migrants should not be considered a homogeneous one; rather, one in which subgroups experience outcomes that are better or worse than, or equal to, those of the comparable native population (Schurer, 2008). Eckstein (2002) argues that migrant generations are influenced by the different social conditions they experience in their pre-and post-migration times.…”
Section: Defining Second-generation Migrantsmentioning
confidence: 99%
“…Current research suggests a stronger ethnic penalty in employment than in schooling or outcomes among the employed (Schurer, 2008), but as concluded by Algan et al (2010: F27), 'more detailed research to investigate the exact mechanisms that lead to the observed disadvantages' is necessary.…”
Section: The Second Generationmentioning
confidence: 98%
“…-In Germany, there seems to be quite important intergenerational progress in economic activity for Turkish second-generation women, even if their levels of activity are lower than that of the native population. On the whole, however, this generation experiences disadvantages in terms of employment, and they tend to earn less (Worbs 2003;Kalter & Granato 2007;Schurer 2008;Liebig 2009). Moreover, second-generation Turks have, albeit with some exceptions, lower returns from education with regard to occupational attainment (Kalter & Granato 2007).…”
Section: Current Empirical Evidencementioning
confidence: 99%